2000
DOI: 10.1038/sj.bmt.1702708
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for long-term engraftment of autologous blood stem cells

Abstract: 38− DR − ), peripheral blood CD34 + cell (PBCD34 + ) count on first apheresis day, or various clinical factors were associated with low blood counts 6 months post ASCT. Thirty-four patients were excluded from analysis either because of death (n = 17) or reinduction chemotherapy prior to 6 months post ASCT (n = 13), or because of lack of follow-up data (n = 4). Of the remaining 136 patients, 46% had low WBC (Ͻ4 × 10 9 /l), 41% low platelets (Ͻ150 × 10 9 /l), and 34% low hemoglobin (Ͻ120 g/l) at a median of 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
2
23
1
2
Order By: Relevance
“…Recent studies in adults have shown that some CD34+ subsets correlated with early or long-term engraftment after autologous PBSCT [9,10,11,12,13,14,15]. In other studies the total dose of CD34+ was a better predictor of hematopoietic engraftment than any CD34+ subset [16,17,18]. But in all these studies the population was heterogeneous with regard to disease, number and type of pre-transplant chemotherapy, mobilization chemotherapy and conditioning regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in adults have shown that some CD34+ subsets correlated with early or long-term engraftment after autologous PBSCT [9,10,11,12,13,14,15]. In other studies the total dose of CD34+ was a better predictor of hematopoietic engraftment than any CD34+ subset [16,17,18]. But in all these studies the population was heterogeneous with regard to disease, number and type of pre-transplant chemotherapy, mobilization chemotherapy and conditioning regimens.…”
Section: Introductionmentioning
confidence: 99%
“…2 The success of auto-HSCT is influenced by a number of factors, with the dose of reinfused stem cells being a key factor. 11 Higher stem cell doses are associated with faster plt engraftment (generally defined as plt count 420 Â 10 9 /l), faster neutrophil engraftment (generally defined as ANC 40.5 Â 10 9 /l) [11][12][13][14][15][16] and reduction in the need for supportive measures such as transfusions of packed RBCs and plts and administration of prophylactic antibiotics. 12,15 In some studies, higher stem cell doses have been associated with higher rates of survival for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Since potency assay could only be completed on 25 samples and two of those would not have been released for transplantation purposes, the accuracy of the assay was approximately 92%. It has been shown that between 15 and 20% of all cord blood stem cell transplants do not engraft [27][28][29]. From the results described here, it would appear that this high percentage rate of graft failure could be reduced by at least 10% thereby significantly improving efficacy and reducing unnecessary risk to the patient.…”
Section: The Relationship Between Stem Cell Potency and "Quality"mentioning
confidence: 67%